Library and Information Service Delivery in Secondary Schools: A Cases Study of St. Pauls S.S in Bukunda Sub-County Kabale District. - Edrida, Katusiime (Kabale University, 2019)
A Research Report Submitted to the Faculty of Arts and Social Science in Partial Fulfillment of the` Award of a Bachelors Degree in Library and Information Science of Kabale University